Calculating Coefficient Correlation and Linear Regression for Advertising Costs and Sales Volume Using Turbo Pascal Version 7.0 - Ali Rachman (Jurnal Sistem Informasi, 2007)
At this writing the cost estimates given of advertising and sales volume of existing companies disuatu using statistical science. Estimates are used to find relationships or linkages between the variables of known values and variables that are not or have not known its value. To obtain an approximate value and is, used a statistical method by using the analysis of the correlation coefficient and linear regression where the buyer is obtained from the existing sample values.